The CHSE paradox: tourists at Blue Lagoon know the rules but do not follow them - Zulhayudin, Muhammad Fadillah; Agustin, Helfi; Marlyta, Nadha; Ruliandari, Rochana; Addini, Ezza (Jurnal Cakrawala Promkes, 2025)
This study examines the relationship between tourists' knowledge of cleanliness, health, safety, and environmental sustainability (CHSE) and their CHSE-related practices at the Blue Lagoon tourist attraction in Sleman, Yogyakarta. Using a cross-sectional design, data were collected from 106 respondents through an accidental sampling technique. The Chi-Square test was employed for statistical analysis. The results revealed no statistically significant correlation between knowledge and CHSE-related practices (cleanliness: p = 0.267, health: p = 0.480, safety: p = 0.724, environmental sustainability: p = 0.257). Despite high levels of knowledge among respondents, this awareness did not necessarily translate into consistent CHSE practices. These findings suggest that factors beyond knowledge, such as behavioral habits, infrastructure availability, and social influences, may be more critical in shaping CHSE practices among tourists. The study has practical implications for improving tourism management by encouraging greater participation from tourism operators in providing adequate CHSE infrastructure, implementing clear regulations, and enhancing supervision. Additionally, tourist compliance with CHSE protocols remains essential for ensuring safety and environmental sustainability in tourism destinations. To strengthen CHSE implementation, advocacy, partnerships, and empowerment programs among stakeholders, including government agencies, tourism managers, universities, media, and the private sector—are crucial. Moreover, policy advocacy should reinforce CHSE compliance through certification mechanisms and sanctions for non-compliance. Continuous and intensive public awareness campaigns are necessary to enhance tourist commitment to CHSE practices, ensuring safer and more sustainable tourism experiences.